If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -9 = 0 + 3 Reorder the terms: -9 + 3y = 0 + 3 Combine like terms: 0 + 3 = 3 -9 + 3y = 3 Solving -9 + 3y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3y = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 3y = 3 + 9 3y = 3 + 9 Combine like terms: 3 + 9 = 12 3y = 12 Divide each side by '3'. y = 4 Simplifying y = 4
| 3m=5.7 | | .4x-9=.1(x+30) | | -1=u-2 | | 52=-2(22-x)+4(x-3) | | 32x^2+18=0 | | (a+1)*(a-3)x=(a+1)*(a+4) | | .8(220-a)=120 | | 2(1+v)=-6+4v | | 117+7y=180 | | 9x^2-18xy-8x+16y=0 | | 15n-6n= | | 3s+s=-49 | | -9.8(27x-65)=78.24(6x+34) | | 4(x-5)-2(x+2)=-22 | | 3e-4=-2 | | 2+14a=-8+9a | | 7y+18=180 | | 60x^2-20xy+12x=0 | | -7(a-6)=2-2a | | 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 | | 6x^3-9x^2-216x+9=0 | | 25=-8+2(s-4) | | 3(a+b)=f | | 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 | | -10(x-1)=-10x | | 0=4x^2+39x-10 |